Reproductive aspects of selected fish species in Mihtsab-Azmati reservoir, Tigray, Northern Ethiopia - Kalayu Mesfin Arefayne; Mekonen Teferi; Tsehaye Asmelash Dejene; Tsegazeabe Hadush Haileselasie (Fisheries and Aquatic Sciences)
Reproduction is a crucial topic in fish biology since it affects both the sustainable production of fish and their wise use. The aim of this study was to generate baseline data on some reproductive biology of commercially important fishes; which was conducted from November 2018 to October 2019 in Mihtsab-Azmati reservoir. A total of four sub-sites (two pelagic and two littoral zones) were selected and depth integrated water quality parameters were collected in-situ. Fish specimens were collected bi-monthly from two pelagic and two littoral sites using standardized experimental multi-mesh gillnets. A total of 2,538 fishes were caught, of this 283 fish specimens belong to Labeobarbus intermedius (n = 174), Oreochromis niloticus (n = 63), Tilapia zillii (n = 24) and Clarias gariepinus (n = 22) were investigated for reproductive analysis. The sex-ratio indicated that males were more numerous than females for most fish species and deviated from the expected 1:1 (female:male). Highest breeding season of O. niloticus, L. intermedius and T. zillii were observed in January. Gonadal maturity stages of the fishes showed that 43% (n = 121) immature, 35% (n = 98) maturing and 20% (n = 58) ripening. Only 2% (n = 6) were categorized mature (gonad stages IV), but there was no any fish species recorded under stage V. The relationship between total length and total weight of the selected fish species were curvilinear and the “b” value exhibits negative allometric growth. The highest and the lowest gonado-somatic index value were recorded in January and May, respectively. Highest mean values of Fulton condition factor were recorded in May (O. niloticus and L. intermedius), in March (C. gariepinus) and in November (T. zillii). We recommend detailed investigation on reproductive aspects of all fish species in the reservoir as the current study only focused on the commercially important fishes.